Concepts about academic advising - Messouda MERIZGUI (Social Sciences Journal, 2021)
The process of counseling and guidance is important for the individual in general, and the individual taught in particular, considering the process aims to help the individual to overcome the problems that he is going through in his school life, as it works to define its characteristics i.e. what it possesses capabilities and skills so that it can be used and used in the learning process, and from During this process, the individual’s vision becomes clear about choosing an appropriate study, as well as an appropriate profession consistent with his capabilities ..., and the individual is in need of this process during the university stage, as it is a crucial period for determining the future, and we have examined in this study the concept of academic guidance, and we also touched on defining the goals of Academic guidance and direction we dealt with the nature of the academic process